CASE STUDY OF THE ORIGIN AND THE EVOLUTION OF ACCOUNTING SYSTEMS REGARDING TO THE HARMONIZATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) IN JORDAN AND ROMANIA - Omar Alhato (University of Oradea, 2021)
It is valuable to take note that the majority of financial reporting pundits are in agreement that the financial reporting system of a country depends on several factors that include the legal, economic, and cultural background; The development of tasks performed by accounting is persistently inspired by needs of practice. It is clear of that accounting schemes play an essential role in the market economy, particularly in face of globalization of capital markets, where increasing need for comparable, transparent financial statements for the companies. Rather, it is proposed to present information that is used in making reasoned options amongst alternative uses of limited resources in the conduct of business and economic activities. The present paper discusses the possibilities to improve the accounting policies and procedures in Jordan and other Middle East countries in accordance with commitment of the International Financial Reporting Standards (IFRS). Throughout this study we used a qualitative approach, to outline an overview of the history of financial reporting and its evolution from the origin, to the growth and development of accounting systems by studying a considerable amount of bibliographic material, using different textbooks and journals on accounting theories but also public information presented by the accounting organisations and the government of the two analysed countries. Furthermore, the paper reviewed the achievements made in the convergence of International Financial Reporting Standards (IFRS), in the Middle East countries, in Jordanian context and in the European Union, specifically the case of Romania. International financial reporting standard (IFRS) implementation in Jordan has departed through several transitional phases wile in our previous work we noticed that Romania can be considered a benchmark of high degree convergence to IFRS.